Clinical Issues for Pediatric Pulmonologists Managing Children With Thoracic Insufficiency Syndrome - Redding, Gregory J. (Frontiers in Pediatrics, 2020)
Thoracic insufficiency Syndrome (TIS) is a recently coined phrase to describe children with spine and chest wall deformities, inherited and acquired, who have respiratory impairment, and are skeletally immature. This population has both restrictive and less often obstructive lung disease due to changes in spine and rib configuration which reduce lung volume, stiffen the chest wall, and reduce respiratory muscle strength. Although the population is heterogeneous with regard to age of onset, etiology, severity of deformity, and rate of progression of the deformity, there are common issues that arise which can be addressed by pediatric pulmonologists. These are illustrated in this review by using Early Onset Scoliosis as a common form of TIS. The pulmonary issues pertaining to TIS require collaboration with multi-disciplinary teams, particularly spine surgeons, in order to make decisions about non-surgical and surgical strategies, timing of surgery and medical supportive care over time. Pulmonary input about respiratory function should be used in conjunction with structural features of each deformity in order to determine the impact of the deformity and the response to various treatment options. In those patients with residual lung function impairment as young adults, pediatric pulmonologists must also ensure successful transition to adult care.